Evaluasi Kesenjangan dan Perancangan Sistem Informasi Berbasis ISO/IEC 9126 (Studi Kasus : Web Indofood) - M Farid Bagaskara; Yola Mutiara; Rianita Nur Afni; Nina Noptrina; Deden Hardan Gutama (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
The importance of a website is determined by how satisfied the user is in accessing and getting information. Software maintenance is also needed to support the quality of the software. Some examples of the positive impacts of improving software quality include profits, reduced costs for maintenance, and increased productivity. one way to test software quality from the product side is using the ISO/IEC 9126 test model using four main assessments, namely usability, functionality, reliability, and efficiency. This standard is a combination of several existing software quality evaluation methods, such as McCall, Boehm, FURPS, and several other methods. So that this model is considered more complete and easier to develop according to research needs because of the description of its general characteristics. The case study in this paper is a website-based software application from Indofood. The results of Indofood's website-based software testing based on ISO 9126, the results for the assessment of usability characteristics got a score of 61%, the assessment of functional characteristics got a score of 66%, the assessment of reliability characteristics got a score of 77% and the assessment of efficiency characteristics got a score of 30%.